TRANSCODIFICAÇÃO: INTERAÇÃO TEXTO VERBAL E IMAGEM (Polifonia, 1995)
ABSTRACT: This study examines illustrations and epigraphs of the "Ciclo da Memória" (1951-1969), a collection of 10 plays by Jorge Andrade, published in 1970. It shows the intertextual counterpoint of those elements in each play and their function of consolidation of the whole collection. It suggests an interpretation of the illustrations as a simulacrum of the dramatist's own view, transcodifying the structural game of approaching  and withdrawing in the aesthetic construction of reality and in the organization of the cicle.